Long term risk of distant metastasis in women with non‐metastatic breast cancer and survival after metastasis detection: a population‐based linked health records study. Issue 8 (20th August 2022) - Lord, Sarah (Sally) J; Daniels, Benjamin; Kiely, Belinda E; O'Connell, Dianne L; Beith, Jane; Pearson, Sallie; Chiew, Kim‐Lin; Bulsara, Max K; Houssami, Nehmat
Abstract: Objectives: To estimate the long term risk of distant metastases (DM) for women with initial diagnoses of non‐metastatic breast cancer; to estimate breast cancer‐specific and overall survival for women with DM. Design: Population‐based health record linkage study. Setting, participants: Women diagnosed with localised or regional primary breast cancer recorded in the NSW Cancer Registry, 2001–2002. Major outcome measures: Time from breast cancer diagnosis to first DM, time from first DM to death from breast cancer. Secondary outcome: time to death from any cause. Results: 6338 women were diagnosed with non‐metastatic breast cancer (localised, 3885; regional, 2453; median age, 59 years [IQR, 49–69 years]). DM were recorded (to 30 September 2016) for 1432 women (23%; median age, 62 years [IQR, 51–73 years]). The 14‐year cumulative DM incidence was 22.2% (95% CI, 21.1–23.2%; localised disease: 14.3% [95% CI, 13.2–15.4%]; regional disease: 34.7% [95% CI, 32.8–36.6%]). Annual hazard of DM was highest during the second year after breast cancer diagnosis (localised disease: 2.8%; 95% CI, 2.3–3.3%; regional disease: 9.1%; 95% CI, 7.8–10.3%); from year five it was about 1% for those with localised disease, from year seven about 2% for women with regional disease at diagnosis. Five years after diagnosis, the 5‐year conditional probability of DM was 4.4% (95% CI, 3.7–5.1%) for women with localised and 10.4% (95% CI, 9.1–12.0%) for those with regional disease at diagnosis. Median breast cancer‐specific survival from first DM record date was 28 months (95% CI, 25–31 months); the annual hazard of breast cancer death after the first DM record declined from 36% (95% CI, 33–40%) during the first year to 14% (95% CI, 11–18%) during the fourth year since detection. Conclusions: DM risk declines with time from diagnosis of non‐metastatic breast cancer, and the annual risk of dying from breast cancer declines with time from initial DM detection. These findings can be used to inform patients at follow‐up about changes in risk over time since diagnosis and for planning health services.